Prevalence, Patterns and Factors Associated with Dyslipidemia Among Adult Hypertensive Patients - Muktar Hassan Mohamud; Awil Abdulkadir Abdi; Abishir Mohamud Hirsi; Ibrahim Ahmed Nur; Alina Peris (BioMed Target Journal)
Dyslipidemia is a major risk factor for coronary heart disease and is responsible for an estimated 2.6 million deaths annually. Hypertensive patients often suffer from dyslipidemia, which can lead to complications such as ischemic heart disease and stroke. This study examined the prevalence and factors associated with dyslipidemia among adult hypertensive patients admitted to Lira Regional Referral Hospital (LRRH) in Uganda. This cross-sectional study, conducted over three months at Lira Regional Referral Hospital (LRRH), involved 431 patients. Medical examinations and histories were recorded, and blood samples were analyzed to measure high-density lipoprotein (HDL), low-density lipoprotein (LDL-c), total cholesterol (TC), and triglycerides (TG). Dyslipidemia was defined by any of the following: TC ≥200 mg/dL, TG ≥150 mg/dL, HDL-C < 40 mg/dL, or LDL-C ≥100 mg/dL. The data were analyzed using binary logistic regression in SPSS version 26 to identify associated factors. A total of 431 patients were included in the study, with the majority being females over 65 years of age (mean age = 64.7, SD = 8.8 years). The prevalence of dyslipidemia was 48.3% (208) (95% CI = 43.2-52.9%). High LDL levels were observed in 24.4% (105), high TC in 22.5% (97), high TG in 20.0% (86), and low HDL in 20.0% (86 patients). Multivariate analysis revealed that patients with elevated blood pressure, stage 1 hypertension, and stage 2 hypertension had 1.350 (aOR = 1.350, CI = 1.194-1.525, P < 0.001), 1.290 (aOR = 1.290, CI = 1.123-1.482, P < 0.001), and 1.302 (aOR = 1.302, CI = 1.077-1.576, P = 0.007) times higher odds of having dyslipidemia, respectively. Additionally, dyslipidemia was 1.414 times more common (aOR = 1.414, CI = 1.280-1.561, P < 0.001) among current or former smokers and 1.493 times more common (aOR = 1.493, CI = 1.372-1.625, P < 0.001) in patients with diabetes mellitus. The findings highlight a high prevalence of dyslipidemia, emphasizing the need for targeted interventions. Enhancing patient education on antihypertensive therapy adherence and increasing efforts to discourage smoking are crucial steps to reduce the burden of dyslipidemia in hypertensive populations.